Penerapan Project-Based Learning Berbasis STEM Dalam Upaya Meningkatkan Literasi Siswa SMA - Hakim, Niswa Karisma; Dhara Citra Putri Setia; Ichsan Fauzi Rachman (STAB Kertarajasa, 2025)
STEM-based Project-Based Learning (PBL) is an effective approach in improving the literacy of high school students in Indonesia. This method encourages students to think critically, collaborate and apply science concepts in real life, resulting in more in-depth and contextualized learning. This research uses a literature study by analyzing various academic sources related to the application of PBL in education. The results show that this method improves students' concept understanding, analytical skills, and problem-solving abilities. Case studies in several schools confirmed the positive impact on academic literacy and critical thinking skills. However, the implementation of this method still faces challenges, such as limited facilities, lack of training for teachers, and variability in student engagement in learning. Support from various parties, including schools, educators and the government, is needed to ensure optimal and sustainable implementation of this method, so that it can contribute to improving the quality of education and students' readiness to face the challenges of the 21st century.